A comparative study on dielectric properties of PVDF/GO nanosheets encapsulated with different organic insulating shell. Issue 14 (22nd September 2021) - Cao, Guozheng; Zhou, Wenying; Kou, Yujia; Li, Ying; Li, Ting; Wang, Yun; Cao, Dan; Wu, Hongju; Wang, Guangheng; Dang, Zhi-Min
ABSTRACT: To suppress the high dielectric loss of graphene oxide (GO)/poly(vinylidene fluoride) (PVDF) while still maintaining a high dielectric constant ( k ) near the filler percolation threshold, herein, GO nanosheets coated with polyvinyl pyrrolidone (PVP), poly(dopamine) (PDA) and tannic and Fe coordination complexes (TA-Fe), respectively, were incorporated into PVDF to investigate the effects of the three kinds of insulating interlayers on the dielectric properties of the nanocomposites. The results indicate that compared with pristine GO, all surface modified GO exhibit homogeneous dispersion in the matrix owing to the enhanced interface between fillers and matrix, and that the dielectric loss of the nanocomposites are significantly suppressed to rather low levels thanks to the presence of various insulating interlayers between GO nanosheets, which prevent them from direct contact, thereby remarkably reducing the leakage current and conductivity. Moreover, Activation energies for the pristine and modified GO/PVDF nanocomposites are calculated, respectively, and the introduction of insulating interlayers significantly reduces the relaxation activation energy of the nanocomposites.